Status of sexual health of married male traumatic paraplegics in Indian Population - Yesh Veer Singh,; Anirudh Chirania,; Vipin Kumar,; Afroz Ahmed Khan,; Abhishek Pandey,; Abhinav Kumar Srivastava, (Asian Journal of Medical Sciences, 2024)
Background: About 1.5 million individuals with spinal cord injuries (SCIs) reside in India. Sixty to seventy percent of the 20,000 new cases of SCI that is added each year are from impoverished, illiterate people. SCI leads to life-altering experiences, encompassing physical, physiological, psychological, and social changes. The sexual orientation of an individual with SCI may directly impact their self-assurance and vice versa. Aims and Objectives: Patients with SCI may have physical, physiological, psychological, and social changes, including changes in their sexuality. After a SCI, individuals’ sexual health is a crucial topic that is rarely addressed. The purpose of this study was to learn about the patients’ experiences and feelings regarding sexual activity after a SCI. Materials and Methods: Patients with SCI were given a questionnaire. This study covered all male SCI patients between the ages of 18 and 50 who were married at the time of the injury and were followed up until December 2023. The purpose of this study was to talk about different facets of sexual activity and the issues that came with it. Second, these data will support SCI sufferer’s sexual rehabilitation. Results: Of the 231 patients, 72.3% had erections but only 32% had ejaculations. 55.8% of patients experienced difficulties with sexual function as a result of other SCI sequelae, such as flexor spasm, bladder, and bowel dysfunction, among others. In response, almost 90% of patients said that they had never received sexual rehabilitation or advice on their sexuality. Conclusion: Health-care providers and clinicians do not frequently bring up sexuality with patients who have SCI. Patients who frequently inquire about sexual activity following SCI yet are seldom helped. Since there is stigma associated with the topic, every SCI clinic needs to have a specialized sexual rehabilitation staff.